Nontraumatic Epithelial Ingrowth 15 Years Post Laser In Situ Keratomileusis - Joanna S. Saade; Baha’ Noureddin; Shady T. Awwad (Case Reports in Ophthalmological Medicine)
Purpose. Epithelial ingrowth occurring many years after primary Laser in Situ Keratomileusis (LASIK) without a preceding traumatic event is very rare. Case Report. We describe the case of a 61-year-old woman with epithelial ingrowth in her right eye 15 years after primary LASIK. She presented with right eye redness, pain, and decreased vision and denied any preceding trauma. An epithelial cells’ tract was visible on Optical Coherence Tomography. Conservative treatment lead to the stabilization of the epithelial nests. Discussion. Epithelial ingrowth can occur many years after LASIK and may be due to a microtrauma to the edge of the flap.